Emergence of Virtual Currencies-Study of Cryptocurrency in Digital Marketing - Minky Sharma (UIN Mataram, 2021)
Present economic scenario is the subject of innovations in all aspect of economy like banking marketing and trade. Digital innovation facilitates the settlement of transactions without presence of individual since virtual currency has also emerged in the way of innovations which facilitate the trading and investment alternatives to the people. Concept of Virtual Currency: Virtual currency or money is a type of unregulated virtual/digital currency which is issued/managed by developers and largely accepted by the members of a virtual community. Definition: According to European Banking Authority (2014), virtual currency is a digital representation of value that is not issued by a banking authority or a public authority, nor essentially attached to a fiat currency, but is accepted by natural or legal persons as a means of payment and can be transferred, stored or traded electronically